Journey into aestheticism: beauty and aesthetic value - Bakoeva Saodat Shuhratovna (Peerian Journals Publishing, 2022)
Aesthetics is the philosophical basis of art, the key to understanding art. Alexander Baumgorten founded the first foundations of aesthetics in the 18th century. The entire system is being reviewed. The most important category in aesthetics was the category of beauty. Throughout the classical era, beauty in art was not a literal reflection of life. The first changes in aesthetics were carried out by artists-poets.
Keywords: carried; philosophical; understanding; entire